Contractile function of fasting and digesting broad-snouted caiman (Caiman latirostris) - Lopes, Andre Guelli [UNESP]; Monteiro, Diana Amaral; Vasconcelos, Eliton da Silva [UNESP]; Kalinin, Ana Lucia (Canadian Science Publishing, 2023)
Feeding regimes are a critical process to ensure survival and reproduction, which modulate several behavioral and physiological patterns of ectotherms, especially cardiovascular adjustments. However, crocodilian myocardial contractile function after food intake remains understudied. We investigated the importance of ventricular myocardial contractility during digestion in the broad-snouted caiman, Caiman latirostris Daudin, 1801. Isometric ventricle preparations and Ca2+-handling protein expression were used to investigate the effects of prolonged fasting (30 days) and feeding (48 h after feeding on meals at 15% of body mass) on cardiac function. Upon feeding, there was no significant difference in relative ventricular mass. The cardiac response of the caiman to digestion was characterized by upregulation of the Na+/Ca2+ exchanger expression and an increase in myocardial contractility (positive inotropism and lusitropism) within the physiological range of heart rate. The digesting caiman's ventricular myocardium was able to maintain faster kinetics of contraction and relaxation, allowing for significantly increased cardiac pumping capacity at higher pacing frequencies. Our results demonstrated that the myocardium of broad-snouted caimans exhibits specializations in excitation-contraction coupling, which can provide a means to support high cardiovascular performance during digestion.
Keywords: broad-snouted caiman; Caiman latirostris; cardiac function; contractile force; digestion; Na plus; Ca2+exchanger; relative ventricular mass